4-Ethylacetophenone from Potato Plants Repels Phthorimaea operculella and Inhibits Oviposition: A Sustainable Management Strategy - Xinyu Ma; Junjie Yan; Guangyuan Su; Fathiya M. Khamis; Athanase Hategekiman; Yulin Gao (Insects)
The potato tuber moth, Phthorimaea operculella (Zeller), is an important pest of potato crops capable of boring into and consuming the potato tubers. Although chemical insecticides are employed to control P. operculella populations, their efficacy is frequently limited, raising environmental concerns. Host plant volatiles are important allelochemicals that can be exploited for the management of pests. In our previous studies, we identified five volatile organic compounds (3-ethylacetophenone, 4-ethylacetophenone, geranylacetone, ethylbenzene, and 4-hydroxy-4-methyl-2-pentanone) as allelochemicals potentially influencing the oviposition behavior of P. operculella. Using electroantennography (EAG) and behavioral assays, we found that 4-ethylacetophenone significantly repelled P. operculella at all tested concentrations (1 μg, 10 μg, and 100 μg; p < 0.05), while 3-ethylacetophenone showed no significant effects (p > 0.05). Finally, the effect of 4-ethylacetophenone on preventing P. operculella from laying eggs was determined by an oviposition selection experiment. Our findings indicate that 4-ethylacetophenone derived from potato plants not only repels P. operculella and prevents egg-laying but also has the potential to reduce the number of eggs, making it a promising green alternative for controlling this pest.